Penerapan Metode Latihan Mandiri Untuk Meningkatkan Hasil Belajar Matematika pada Siswa SMP Negeri 1 Kayangan - Wahyuningsih, Wiwiek Sriwiarti (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2019)
The aim of this study was to Â improve the studentsâ€™ mathematics learning outcomes of SMPN 1 Kayangan through the application of the Independent training method. This research used classroom action research by applying the model developed by Kemmis and Mc. Taggart. This research was conducted in class VIII.1 of SMPN 1 Kayangan in the Even Semester of the 2018/2019 school year. Data collection instruments used were observation sheets, test, and documentation. The data analysis technique of this study used qualitative and quantitative descriptive analysis techniques. The result of the study showed that the studentsâ€™ mathematics learning outcomes by applying the Independent training method in cycle 1 was 65.2% and cycle 2 was 85.2%. Meanwhile, the average cycle test results were 70.2 and cycle 2 was 81.4. This result indcated an increase in student learning outcomes. From this classroom action research, it can be concluded that Independent training can improve the studentsâ€™ mathematics learning outcomes of SMP Negeri 1 Kayangan.